Orfeu da Conceição: ressignificação do mito a partir da carnavalização do trágico - Costa, Michel de Lucena (2014)
This research aims to analyze the Orfeu da Conceição play (1956) by Vinícius de Moraes, understanding it as a carnivalized tragedy. To formalize this paper, a semiotic study will be conducted to understand how the process of redefinition of Greek myth occurred from the perspective of Bakhtin carnivalization. Having the Semiotics of Culture as theoretical and methodological support, the elements ranging from Greek tragedy and religion to the samba origin, their relationship with Candomblé, coming to an understanding of the twentieth century Brazilian theater will be studied. The Semiotics of Culture will help us understand how the process of "translation tradition" occurred, ie the adaptation of the Greek myth into the hillside home in the 1950s, roaming the fields of dramatic text and music. Finally, with this dissertation, it is expected to have contributed to the field of semiotic studies applied to the theater.